Immunosuppressive therapy and the risk of hepatitis B reactivation: Consensus report - Aygen, Bilgehan; Demir, Ahmet Muzaffer; Gümüş, Mahmut; Karabay, Oğuz; Kaymakoğlu, Sabahattin; Köksal, Aydın Şeref; Köksal, İftihar; Örmeci, Necati; Tabak, Fehmi (Turkish Journal of Gastroenterology, 2018)
Abstract This consensus report includes expert opinions and recommendations regarding the screening, and if necessary, the follow-up, prophylaxis, and treatment of hepatitis B before the treatment in patients who will undergo immunosuppressive therapy due to an emergency risk of hepatitis B reactivation. To increase awareness regarding the risk of hepatitis B reactivation in immunosuppressive patients, academicians from several university health research and training centers across Turkey came together and discussed the importance of the subject, current status, and issues in accordance with the current literature data and presented solutions. Cite this article as: Aygen B, Demir AM, Gümüş M, et al. Immunosuppressive therapy and the risk of hepatitis B reactivation: Consensus report. Turk J Gastroenterol 2018; 29: 259-69.